Gibberellin biosynthesis inhibitors distinctly affect sunflower morphometric and growth dynamics - Mendes, Carolina Ruv Lemes Gonçalves [UNESP]; Ferreira, Lusiane de Sousa [UNESP]; Carnietto, Melina Rodrigues Alves [UNESP]; Almeida, Laura Costa Oliveira [UNESP]; da Silva, Gustavo Ferreira [UNESP]; Santos, Hariane Luiz [UNESP]; Boaro, Carmen Sílvia Fernandes [UNESP]; Silva, Marcelo de Almeida [UNESP] (Elsevier, 2025)
Evaluating the growth characteristics of plant cultivars and their interaction with the technologies adopted to control phenotypic characteristics is paramount in understanding the phenomena that occur in various phenological phases. The use of plant growth regulators (PGR) can help solve the problem of lodging. Thus, the premise of this research is that management with different gibberellin biosynthesis inhibitors promotes the control of plant height and stem diameter phenotypic characteristics and interferes with the sunflower crop's growth behavior. The research was carried out in the field over two crop seasons, 2020/2021 and 2021/2022, in a randomized block design, with subdivided plots consisting of two sunflower cultivars, TERA 868 HO and HELIO 251, three gibberellin biosynthesis inhibitors (trinexapac-ethyl, chlormequat chloride, and paclobutrazol) and control, with four replicates. Evaluations measuring plant height and stem diameter and growth analysis were taken. Depending on the cultivar, plant growth regulator, and evaluation period, plant height, stem diameter, and growth analysis were affected differently. Trinexapac-ethyl and chlormequat chloride induced a more pronounced decrease in TERA 868 HO height at 30 and 45 DAA in the 2021/22 crop season while concurrently fostering an increase in HELIO 251 stem diameter in the 2021/22 crop season compared to the other treatments. Regarding growth, decreases were observed in absolute growth rate, relative growth rate, and net assimilation rate, as well as increases in leaf area ratio. The most significant expression of the effects occurred 30 days after application (DAA) under trinexapac-ethyl and chlormequat chloride.
Keywords: Biometric variables; Gibberellin modulation; Growth analysis; Helianthus annuus l.; Plant height